High Mass-Loading of Sulfur-Based Cathode Composites and Polysulfides Stabilization for Rechargeable Lithium/Sulfur Batteries - Hara, Toru; Konarov, Aishuak; Mentbayeva, Almagul; Kurmanbayeva, Indira; Bakenov, Zhumabay (Frontiers in Energy Research, 2015)
Although sulfur has a high theoretical gravimetric capacity, 1672 mAh/g, its insulating nature requires a large amount of conducting additives: this tends to result in a low mass-loading of active material (sulfur), and thereby, a lower capacity than expected. Therefore, an optimal choice of conducting agents and of the method for sulfur/conducting-agent integration is critically important. In this paper, we report that the areal capacity of 4.9 mAh/cm2 was achieved at a sulfur mass loading of 4.1 mg/cm2 by casting sulfur/polyacrylonitrile/ketjenblack (S/PAN/KB) cathode composite into carbon fiber paper. This is the highest value among published/reported ones even though it does not contain expensive nano-sized carbon materials such as carbon nanotubes, graphene, or graphene-derivatives, and competitive enough with the conventional LiCoO2-based cathodes (e.g., LiCoO2, <20 mg/cm2 corresponding to <2.8 mAh/cm2). Furthermore, the combination of sulfur/PAN-based composite and PAN-based carbon fiber paper enabled the sulfur-based composite to be used even in carbonate-based electrolyte solution that many lithium/sulfur battery researchers avoid the use of it because of severer irreversible active material loss than in electrolyte solutions without carbonate-based solutions, and even at the highest mass-loading ever reported (the more sulfur is loaded, the more decomposed sulfides deposit at an anode surface.).